Effect of Nutrient Management on Dry Matter Production and Nutrient Uptake of Hyacinth bean in Baby corn (Zea mays L.) – Hyacinth bean (Lablab purpureus var. typicus) Cropping System - Preetham, R.; Kumar, K. Avil; Srinivas, A.; Rao, A. Manohar; Ramprakash, T. (International Journal of Bio-resource and Stress Management, 2020)
The field experiments were conducted at Horticultural Research Station, SKLTSHU, Adilabad, Telangana State, India during rabi seasons (October-February) of 2015-16 and 2016-17 to study the effect of Integrated Nutrient Management practices on dry matter production and nutrient uptake of hyacinth bean in baby corn–hyacinth bean cropping system. Experiment was laid in Randomized Block Design for baby corn during kharif 2015 with seven treatments comprised of 100 % recommended dose of fertilizers (RDF 150:60:60 N, P2O5 and K2O kg ha-1), 25 % N supplemented through farm yard manure or vermicompost+75% RDF with or without bio-fertilizers Azospirillum and Bacillus megaterium @ 5 kg ha-1 each in addition to control and replicated thrice. Each main treatment was divided into four subplots and the treatments of 100% RDF (20-50 N, P2O5 kg ha-1) and 75% RDF with or without Bradyrhizobium @ 500 g ha-1 (seed treatment) were imposed for hyacinth bean in rabi season and data of rabi 2015-16 and 2016-17 was analyzed in split plot design. Application of 25% N through FYM in conjunction with 75% RDF and bio-fertilizer to baby corn during kharif and 100% RDF along with seed treatment with Bradyrhizobium to hyacinth bean during rabi resulted in significantly higher dry matter production at various growth stages and nutrient uptake (nitrogen, phosphorus and potassium) over rest of the treatments.